Islamic Law on Mediation in Indonesia; Position and Strategy - Siti Marlina (International Journal of Southeast Asia, 2021)
This paper is about Islamic Law on Mediation in Indonesia; Position and Strategy. Islamic law in the context of its position and strategy towards national law becoming positive law has sparked ongoing controversy since independence until now. The various strategies and explanations about them give a special style to the peculiarities of Islamic legal thought in Indonesia. This paper focuses on how the position and strategy of Islamic law in the positivization of law in Indonesia. The plurality of Indonesian law, which is a necessity, becomes a positive partner for Islamic law towards the positivization of legal law nationally. The strategy taken is to unite perceptions which are the substance of Islamic teachings in the meaning of sharia and fiqh in the form of universality values that exist in Islam such as the substance of justice, honesty, equality, balance and the like. The concept of mediation in Islamic law must be in accordance with PERMA No. 1 of 2016, its position and strategy. Mediation is nothing more than facilitating the negotiation process, where a mediator tries to help the parties negotiate effectively and efficiently so that they can reach the decisions they want. There are two simple rules for mediators proposed by Stitt, namely the first is do no harm.